Switching to risankizumab from ustekinumab or adalimumab in plaque psoriasis patients improves PASI and DLQI outcomes for sub-optimal responders. (3rd October 2022) - Strober, Bruce; Armstrong, April; Rubant, Simone; Patel, Manish; Wu, Tianshuang; Photowala, Huzefa; Crowley, Jeffrey
Abstract: Background: Psoriasis is often treated with biologic therapies. While many patients see improvement in their symptoms with treatment, some achieve only partial success. Objective and Methods: In this post-hoc analysis we assess Psoriasis Area Severity Index (PASI) and Dermatology Life Quality Index (DLQI) results from patients who switched to RZB due to suboptimal results that originally received ADA ( N = 53, IMMvent NCT02694523) or UST ( N = 172, UltIMMa-1 [NCT02684370], UltIMMa-2 [NCT02684357]). Results: For patients originally treated with ADA, after three doses of RZB, 83.3% of PASI 50 to <75 patients improved to PASI ≥75 and for PASI 75 to <90 patients, 77.1% improved to PASI ≥90. For patients originally treated with UST, after 7 doses of RZB, 86.8% of PASI <75 patients improved to PASI ≥75 and 75.5% of PASI 75 to ≤90 patients improved to PASI ≥90. No patients demonstrated worsening from their initial PASI group after switching. There were no significant safety events associated with switching patients to RZB without a washout period. Conclusion: For patients with an inadequate or incomplete response to UST or ADA, switching to RZB improved PASI scores and DLQI for patients with moderate to severe plaque psoriasis with no significant safety risks.